TIME DOMAIN ANALYSIS OF HEART RATE VARIABILITY IN PATIENTS WITH CORONARY ARTERY DISEASE - Mubarak, Sadia; Majeed, Muhammad Imran; Khan, Muhammad Alamgir (Pakistan Journal of Physiology, 2014)
Background: Heart rate variability is a non-invasive predictive marker of ventricular arrhythmias. Heart rate variability quantifies autonomic nervous system which underlies development of ventricular arrhythmias. Reduced heart rate variability is an indicator of high risk for ventricular arrhythmogenesis. Patients with coronary artery disease may develop ventricular arrhythmias which may lead to sudden cardiac death. Current study was planned to carry out time domain analysis of heart rate variability in patients with coronary artery disease. Methods: Forty patients having coronary artery disease with at least one stenotic lesion of greater than 70% of the vessel lumen were included. Patients with diabetes mellitus, atrial fibrillation, structural heart diseases and bundle branch block were excluded. DMS 300 4A Holter monitors were used to obtain long-term 12-lead digital ECG recordings. CardioScan premium luxury software was used for analysis of heart rate variability. Results: The mean values of heart rate variability in patients were SDNN (102.15±3.66 ms), SDNNi (45.83±11.09 ms), SDANN (90.45±24.66 ms), RMSSD (24.98±7.26 ms) and pNN50 (6.88±6.12 ms). On comparison with normal reference values there was a significant decrease (p<0.05) in all parameters except RMSSD (p=0.145). SDNN was decreased in 38 (88%), SDANN in 36 (83%), SDNNi in 28 (70%), RMSSD in 27 (68%) and pNN50 in 25 (63%) patients. The difference between frequency of patients with decreased heart rate variability was statistically significant (p<0.05) except pNN50 (p=0.155). Conclusion: Heart rate variability decreases significantly in patients with coronary artery disease as compared to normal reference values taken from healthy individuals. Pak J Physiol 2014;10(1-2):21–4